The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/mnfr.202000811
|View full text |Cite
|
Sign up to set email alerts
|

Western Diet Aggravated Carbon Tetrachloride‐Induced Chronic Liver Injury by Disturbing Gut Microbiota and Bile Acid Metabolism

Abstract: Scope The high‐fat, high‐sucrose, and low‐fiber Western diet (WD) is popular in many countries and affects the onset and progression of many diseases. This study is aimed to explore the influence of the WD on chronic liver disease (CLD) and its possible mechanism. Methods and results C57BL/6 mice are given a control diet (CD) or WD and CLD is induced by intraperitoneally injecting carbon tetrachloride (CCL4) twice a week for 8 weeks. The WD aggravated CCL4‐induced chronic liver injury, as evidenced by increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…A previous study showed that alteration in BA hydrophobicity through BSH deconjugating induced the expression of key genes related to lipid metabolism and transportation [ 51 ]. Supporting evidence showed that the abundances of Lactobacilli and Bifidobacterium had positive correlations with the secondary/primary BA ratio [ 52 ], and the abundance of Firmicutes was negatively associated with the secondary/primary BA ratio. Our results are consistent with the above-mentioned results that the abundance of Bifidobacterium increased in FLA-fed groups (middle and high dose) and Firmicutes decreased in all FLA-fed groups.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that alteration in BA hydrophobicity through BSH deconjugating induced the expression of key genes related to lipid metabolism and transportation [ 51 ]. Supporting evidence showed that the abundances of Lactobacilli and Bifidobacterium had positive correlations with the secondary/primary BA ratio [ 52 ], and the abundance of Firmicutes was negatively associated with the secondary/primary BA ratio. Our results are consistent with the above-mentioned results that the abundance of Bifidobacterium increased in FLA-fed groups (middle and high dose) and Firmicutes decreased in all FLA-fed groups.…”
Section: Discussionmentioning
confidence: 99%
“…Bile acids (TCA, taurocholic acid; βMCA, β-muricholic acid; CA, cholic acid; αMCA, α-muricholic acid; UDCA, ursodeoxycholic acid; CDCA, chenodeoxycholic acid; DCA, deoxycholic acid; ωMCA, ω-muricholic acid; HDCA, hyodeoxycholic acid; muroCA, murocholic acid; βDCA, β-deoxycholic acid; and LCA, lithocholic acid) in colon contents were detected according to previously described protocol ( Xie et al, 2015 ; Yang et al, 2021 ) and purchased from Steraloids, Inc. (Newport, RI, United States). Briefly, colon contents were mixed with 200 μL acetonitrile/methanol (volume 8:2), which contained internal standards (GCA-d4, TCA-d4, GDCA-d4, CA-d4, DCA-d4, and LCA-d4).…”
Section: Methodsmentioning
confidence: 99%
“…30 Yang et al revealed that Bacteroidetes were enriched in the mouse model of fibrosis induced by a western diet combined with CCl4, while Firmicutes decreased. 31 Bajaj et al found a direct relationship between patients with cirrhosis and levels of Lactobacillaceae and Bifidobacterium. 9 Chen et al found that the degree of liver fibrosis is positively correlated with the richness of streptococcaceae but negatively correlated with the richness of Lachnospiraceae.…”
Section: Discussionmentioning
confidence: 99%